Postharvest Analysis of Lowland Transgenic Tomato Fruits Harboring hpRNAi-ACO1 Construct. (31st July 2012) - Behboodian, Bita; Mohd Ali, Zainon; Ismail, Ismanizan; Zainal, Zamri
Abstract : The plant hormone, ethylene, is an important regulator which involved in regulating fruit ripening and flower senescence. In this study, RNA interference (RNAi) technology was employed to silence the genes involved in ethylene biosynthetic pathway. This was achieved by blocking the expression of specific gene encoding the ACC oxidase. Initially, cDNA corresponding to ACO1 of lowland tomato cultivar (MT1), which has high identity with ACO1 of Solanum lycopersicum in GenBank, was cloned through RT-PCR. Using a partial coding region of ACO1, one hpRNAi transformation vector was constructed and expressed ectopically under the 35S promoter. Results showed that transgenic lines harboring the hpRNA- ACO1 construct had lower ethylene production and a longer shelf life of 32 days as compared to 10 days for wild-type fruits. Changes in cell wall degrading enzyme activities were also investigated in cases where the transgenic fruits exhibited reduced rates of firmness loss, which can be associated with a decrease in pectin methylesterase (PME) and polygalacturonase (PG) activities. However, no significant change was detected in both transgenic and wild-type fruits in terms of β -galactosidase ( β -Gal) activity and levels of total soluble solid, titratable acid and ascorbic acid.